Programa habitacional minha casa, minha vida: uma análise dos contratos em Santana do Livramento / RS - (:unkn) unknown (Universidade Federal do Pampa, 2018)
The Minha Casa Minha Vida Program, released by the Brazilian Federal Government in 2009, is one of the largest initiatives in the fight against the housing deficit of more than 6,000,000 housing units. The results obtained through the research carried out confirm this assertion, using the city of Santana do Livramento/RS as a place of analysis, which presents a history of few programs directed to the promotion of housing and social welfare. The research used the documental analysis methodology of the contracts registered and filed in the Registry of Real Estate of the city, from 2009 to the first half of 2018. Annual non-payment volumes were verified to determine program performance and data registered contracts, observing the substantial decrease in contracting in the last three years.
Minha casa minha vida program: an analysis of contracts in Santana do Livramento / RS
Keywords: Programa minha casa, minha vida; Habitação; Contratos habitacionais; Caixa Econômica Federal; Minha casa, minha vida programs; Housing contracts; CNPQ::CIENCIAS SOCIAIS APLICADAS